Plasticizers in the neonatal intensive care unit: A review on exposure sources and health hazards - Panneel, Lucas; Malarvannan, Govindan; Jorens, Philippe G.; Covaci, Adrian; Mulder, Antonius (Critical reviews in environmental science and technology, 2022)
Plasticizers, used to increase the flexibility of plastic materials, can leach into the environment and the human body. Various adverse health effects are attributed to exposure to plasticizers, particularly phthalates. Premature newborns admitted to a neonatal intensive care unit (NICU) are exposed to many indwelling plastic devices containing plasticizers while in a developmentally vulnerable period. This is the first comprehensive review of its kind, providing an overview of DEHP and alternative plasticizers (APs), their sources and degree of exposure in the NICU, and the resulting health risks in (premature) infants. Despite the 2017 EU Medical Devices Regulation (2017/745), di-(2-ethylhexyl) phthalate (DEHP) is still a commonly present plasticizer in plastic medical devices in the NICU, with current labeling being insufficient to guarantee absence. Estimated NICU exposures remain elevated above the tolerable daily intake. Medical procedures leading to the highest exposure of phthalates and APs, are extracorporeal membrane oxygenation, blood transfusion, parenteral nutrition and respiratory support. As traditional matrices, such as blood and urine, are not always readily available in neonates, the accumulation of plasticizers in alternative matrices, such as hair and nails, provides an opportunity to study long-term accumulation of toxic chemicals. Impaired respiratory and neurodevelopment correlate with phthalate exposure at both biological and epidemiological levels in childhood, yet knowledge gaps about the effects in neonates prevail. Some APs provide interesting opportunities to reduce toxicity, but human data regarding health effects remain limited. Although toxicologists and regulators have addressed the problem for some time, awareness is lacking mainly among healthcare professionals.